2017
DOI: 10.1007/s12094-017-1756-5
|View full text |Cite
|
Sign up to set email alerts
|

Oncologist’s knowledge and implementation of guidelines for breakthrough cancer pain in Spain: CONOCE study

Abstract: Despite oncologist's clinical practice is increasingly guided by GPC, it suffers from limited compliance, at least in part due to suboptimal statements. Improved dissemination and education are needed to enhance guideline implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Second is the unconsciousness or low compliance of medical members to guideline. Recent study showed despite oncologist's clinical practice on BTP treatment was increasingly guided by clinical guideline, it suffers from limited compliance [ 45 ]. Our study indicated improved dissemination and education were needed to enhance the awareness and guideline implementation in Chinese context.…”
Section: Discussionmentioning
confidence: 99%
“…Second is the unconsciousness or low compliance of medical members to guideline. Recent study showed despite oncologist's clinical practice on BTP treatment was increasingly guided by clinical guideline, it suffers from limited compliance [ 45 ]. Our study indicated improved dissemination and education were needed to enhance the awareness and guideline implementation in Chinese context.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that adherence to guidelines may be improved through the standardisation of processes and the development of protocols . Another widely reported barrier was lack of resources, such as lack of time and heavy workload . This barrier can be overcome by the provision of sufficient time to use the guidelines in practice …”
Section: Resultsmentioning
confidence: 99%
“…Además, a pesar de la prevalencia y de ser un factor pronóstico negativo en pacientes oncológicos, el DIO está infradiagnosticado y poco tratado. Un estudio cualitativo realizado en España para determinar la adherencia a la Guía Clínica del Tratamiento del Dolor Oncológico de la Sociedad Española de Oncología Médica (38) mostró que, aunque los oncólogos (n = 83) fueron unánimes en la necesidad de tratamiento específico para el DIO (100 %), y en el uso de fentanilo como fármaco de primera elección (99 %), la guía adolece de un cumplimiento limitado, en parte debido a su baja difusión y en parte a la posible confusión en ciertas recomendaciones (39). Asimismo, un estudio realizado con oncólogos americanos mostró que una de las barreras identificadas para el tratamiento adecuado del dolor era la necesidad de formación específica en este campo (40).…”
Section: Discussionunclassified